DIDACTIC AND MOTIVATION OPPORTUNITIES OF USING VARIABLE APPROACHES IN IMPROVING PROFESSIONAL COMPETENCE OF FUTURE DEFECTOLOGISTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article explains that practical training is a process designed to solve various practical problems in terms of its content and essence. the main directions of the training and the didactic and motivational possibilities of using different approaches in the preparation of future defectologists for inclusive education.